Pelatihan Dan Pendampingan Membuka Usaha Kecil Menuju Kemandirian Ekonomi Di Rumah Tahfizd Qur’an Al-Mahirah Kota Pekanbaru - Eka Komalasari; Meirinasuri, Dia; Nurmasari (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
This service aims to identify problems with the Tahfizd Qur'an Al-Mahirah House in Pekanbaru City and be able to provide solutions. The trial found that from the funding aspect, the manager of the Al-Mahirah Tahfizd Qur'an House does not yet have a permanent donor, besides that partners do not have a permanent job. Second: the promotion aspect, the promotion of the Tahfizd Qur'an Al-mahirah House must be carried out again considering that the Tahfizd House has moved to lease. The method used has three stages: observation and discussion, training and mentoring, and the application of technology. The results of this service activity are from the funding aspect the Community Service Team provides training and assistance to open small businesses at home such as Frozen Food businesses. Promotional elements The Community Service Team helped make the Rumah tahfizd logo, make banners and assist with promotions on social media. It is hoped that the alternative solutions provided in this Community Service activity will make the Tahfizd Qur'an Al-Mahirah House more economically independent and be able to carry out more activities to support the activities of the Al-Mahirah Tahfizd Qur'an House.